TAXONOMIC AND MOLECULAR CHARACTERIZATION OF FUNGI FROM SUGARCANE BAGASSE - Villalobos, Carlos E.; Gordillo, Marisol; Chaurra, Adriana; Navia, Diana P. (Chilean Journal of Agricultural & Animal Sciences, 2024)
Agroindustrial waste represents an important source of energy for various species of fungi that can establish themselves in waste and use it as a substrate. In this study, a macrofungus that grows in the wild on sugarcane bagasse produced by the paper industry was taxonomically identified. Ten samplings or mushroom collections were made at the site, and an average of 6 individuals were collected per sampling. Specimens had a pileus between 4 and 15 cm in diameter, from parabolic to convex in shape, slightly umbilicated with soft odor and fibrous texture, brown on the surface and paler towards the margin, with tight lamellae of various lengths, ventricles, free union to stipe, and brown and pink in color. These characteristics allowed the identification of the specimens within the Volvariella genus. Molecular analyses using DNA sequencing of the basidia of the fungus allowed making comparisons with other Volvariella sequences stored in GenBank. A tree was generated by the maximum-likelihood method using the nucleotide substitution model HKY + I + G with 2.815 as the alpha parameter of the gamma distribution and 0.2990 as the proportion of invariant sites. The nucleotide frequencies were T = 0.2812, C = 0.2741, A = 0.2076, and G = 0.2372, while the phylogenetic reconstruction identified the species as Volvariella volvacea, with a 100% bootstrap. This is the first report of V. volvacea in southwestern Colombia and highlights the importance of the ligninolytic potential of this species as a food source and bioremediating agent.